2018
DOI: 10.1007/978-1-4939-8663-7_17
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model for Genetic Analysis of Multi-Gene Families: Cloning and Transgenesis of Large Tandemly Repeated Histone Gene Clusters

Abstract: Histone post-translational modifications (PTMs) are thought to participate in a range of essential molecular and cellular processes, including gene expression, replication, and nuclear organization. Importantly, histone PTMs are also thought to be prime candidates for carriers of epigenetic information across cell cycles and generations. However, directly testing the necessity of histone PTMs themselves in these processes by mutagenesis has been extremely difficult to carry out because of the highly repetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Engineered 5-kb histone repeats were then arrayed to 12 copies in pMultiBac ( McKay et al. , 2015 ; Meers et al , 2018 ). All histone gene arrays were inserted into the VK33 attP site on chromosome 3L (65B2) ( Venken et al.…”
Section: Methodsmentioning
confidence: 99%
“…Engineered 5-kb histone repeats were then arrayed to 12 copies in pMultiBac ( McKay et al. , 2015 ; Meers et al , 2018 ). All histone gene arrays were inserted into the VK33 attP site on chromosome 3L (65B2) ( Venken et al.…”
Section: Methodsmentioning
confidence: 99%
“…All experimental animals were raised at 25°C. Details regarding construction of bacterial artificial chromosome (BAC) transgenes containing the 12xH3.2 histone gene arrays can be found here (10). The 12x HWT, K27R, K36R, K9R alleles were generated previously (9,13).…”
Section: Drosophila Lines and Husbandrymentioning
confidence: 99%
“…In animal cells, histone PTM functions have largely been inferred from genetic analyses of histone modifying factors (readers, writers, erasers), rather than from studying the histone residues themselves. To help decipher the metazoan 'histone code' (8), we developed an experimental system in Drosophila that allows for sophisticated phenotypic analysis following loss of a specific site of histone modification (9,10). Interestingly, we found that histone missense mutants often exhibit a subset of the phenotypes caused by mutations in their cognate chromatin-modifying enzymes (9,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy allows us to engineer histone genotypes encoding mutant histone proteins in which a given residue is changed to one that is not a substrate for its cognate modifying enzyme. 5,41,[49][50][51][52]65,66 Using this strategy, we demonstrated previously that H4 K20A mutant animals can survive to adulthood 49 (Figure 5C, D). By contrast, 100% of Set8 20/20 null animals die as larvae or early pupae 40 (Figure 2C).…”
Section: Mutants Of H4k20 and Set8 Are Phenotypically Distinctmentioning
confidence: 71%
“…This strategy allows us to engineer histone genotypes encoding mutant histone proteins in which a given residue is changed to one that is not a substrate for its cognate modifying enzyme. 5,41,4952,65,66…”
Section: Resultsmentioning
confidence: 99%